An Analysis of the Endogamous Marriage of the Ahmadiyya Jama'at as a Minority Islamic Group: The Perspective of Maqasid al-Syari'ah Jamaluddin 'Atiyyah - Muhammad Waliyuddin Yusuf; Moh. Wahib; Athifa Aulia Fika Navila (Jurnal Hukum Prasada, 2026)
This study examines the practice of endogamous marriage within the Ahmadiyya Jama'at as a minority Islamic community in Indonesia through the framework of Maqasid al-Syari‘ah formulated by Jamaluddin ‘Atiyyah. The research is grounded in the socio-religious reality that endogamy functions as a strategic mechanism to preserve religious identity, reinforce internal solidarity, and ensure community continuity amid stigma, discrimination, and pressure from the mainstream Muslim population. However, this practice also raises normative concerns, particularly regarding potential limitations on individual autonomy in spouse selection, internal power relations, gender implications, and its broader impact on justice and welfare in Islamic legal thought. Using normative legal research with a qualitative library-based approach, this study analyzes classical and contemporary maq??id literature, Islamic family law, and relevant scholarly works. The findings indicate that Ahmadiyya endogamous marriage generally aligns with family-oriented maq??id, especially in protecting religion (?if? ad-d?n), preserving lineage (?if? an-nasl), safeguarding nasab, maintaining marital harmony, ensuring institutional family stability, and supporting economic security. Nevertheless, potential mafsadat may arise when the practice is applied coercively or undermines individual dignity and freedom of choice. The study emphasizes the importance of safeguarding free consent, protecting individual rights within minority communities, and promoting proportional and ethical implementation. For policymakers, a maq??id-based evaluative approach may help ensure that minority religious practices remain consistent with principles of justice, non-discrimination, religious freedom, and human rights within the national legal framework.